The Metaphors of Conscientia in Seneca's Epistles. - Németh, Attila (Mnemosyne, 2023)
Seneca's masterful application of metaphors often illuminates some Stoic technical terminology in contexts, which render them meaningful and familiar to his Roman readers. In this paper I argue that in certain instances, these metaphors are also used to organize whole systems of concepts that refer to an essential theoretical component of Seneca's philosophy. By studying the literary and philosophical context of these metaphors, I reconstruct Seneca's requirement for moral self-improvement in his Epistles and propose that his conception of conscientia or 'moral conscience'—a notion scattered throughout his writings but which, as the examination of his systematic metaphors will prove, has a consistent, identical function everywhere it appears—points to some novel rational characteristics of the philosopher's conception of the self.